Three-Dimensional Structure and Determinants of Stability of the Iron-Sulfur Cluster Scaffold Protein IscU from Escherichia coli - Kim, Jin Hae (2012)
The highly-conserved protein, IscU, serves as the scaffold for iron-sulfur cluster assembly in the ISC system common to bacteria and eukaryotic mitochondria. The apo-form of IscU from Escherichia coli has been shown to populate two slowly interconverting conformational states: one structured (S) and one dynamically disordered (D). Furthermore, single-site amino acid substitutions have been shown to shift the equilibrium between the metamorphic states. Here, we report three-dimensional structural models derived from NMR spectroscopy for the S-state of wild-type (WT) apo-IscU, determined under conditions where the protein was 80% in the S-state and 20% in the D-state, and for the S-state of apo-IscU(D39A), determined under conditions where the protein was ~ 95% in the S-state. We have used these structures in interpreting the effects of single site amino acid substitutions that alter %S = (100×[S])/([S]+[D]). These include different residues at the same site, %S: D39V > D39L > D39A > D39G ≈ WT, and alanine substitutions at different sites, %S: N90A > S107A≈E111A > WT. Hydrophobic residues at residue 39 appear to stabilize the S-state by decreasing the flexibility of the loops that contain the conserved cysteine residues. The alanine substitutions at positions 90, 107, and 111, on the other hand stabilize the protein without affecting the loop dynamics. In general, the stability of the S-state correlates with the compactness and thermal stability of the variant.